INVESTIGATION IN MONEY LAUNDRY CRIMINAL ACT - I Putu Kardianto (Fakultas Hukum Universitas Mataram, 2015)
The Poltical law aspect contained in the Investigation of Money Laundry Criminal Acts (MLCA) will be effective if it based on the idea of Article 74 UUTPPU. Its aim to facilitate investigator in the search of the crime assets, which is inseparably part of evidences collection in an investigation process as regulated in Article 183 Jo 184 of the Code of Criminal Law Proceeding (KUHAP) and Article 73 of MLCA concerning the valid evidence instrument. The un-optimal application of Article 74 of the MLCA in Particular Criminal Detective Unit (DIT RESKRIMSUS) of West Nusa Tenggara Police department mainly caused by the limited access to information and the lack cooperation between investigators and PPATK. Whereas, main props of the MLCA investigation are law enforcers and investigation supporting facilities. Hence, it requires a more certain regulation and well-skilled-intellectual investigators in order to optimized the implementation of Law number 8 of 2010.Keywords: Investigation, Crime, Money Laundry